1996
DOI: 10.1097/00005131-199601000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Reinforcement of Cancellous Bone Screws with Calcium Phosphate Cement

Abstract: The ability of calcium phosphate cement (CPC) to reinforce cancellous screws placed in previously stripped holes was studied in vitro. The distal end of canine femurs were harvested. A total of 15 screws were placed in six femurs. The pullout strength (failure force), failure displacement, stiffness, and energy absorbed were determined for the screws in the intact cancellous bone. Next, these stripped screw holes were packed with CPC. The pullout test was repeated, and the results were compared using a paired,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Besides, other successful attempts have been made to use these formulations for calcaneal fractures [509], hip fractures [510,511], augmentation of osteoporotic vertebral bodies [512], distal radius fractures [513], tibial plateau fractures [33,[513][514][515][516][517], restoration of pedicle screw fixation [518,519], reinforcement of thoracolumbar burst fractures [520], cancellous bone screws [521,522], in wrist arthrodesis [523] and for fixation of titanium implants [524]. A recent study on a cement augmentation of the femoral neck defect might be found elsewhere [525].…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%
“…Besides, other successful attempts have been made to use these formulations for calcaneal fractures [509], hip fractures [510,511], augmentation of osteoporotic vertebral bodies [512], distal radius fractures [513], tibial plateau fractures [33,[513][514][515][516][517], restoration of pedicle screw fixation [518,519], reinforcement of thoracolumbar burst fractures [520], cancellous bone screws [521,522], in wrist arthrodesis [523] and for fixation of titanium implants [524]. A recent study on a cement augmentation of the femoral neck defect might be found elsewhere [525].…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%
“…However, the use of CPC in low-quality cancellous bone to enhance screw purchase is less well described although the technique has proven to significantly reduce the frequency of complications such as loosening and migration (Mermelstein et al, 1996;Andreassen et al, 2004). In hip fractures, small amounts of CPC have been shown to enhance conventional hip fracture screw purchase and to increase the fracture construct stiffness and minimize hip fracture screw displacement (Stankewich et al, 1996;Elder et al, 2000;von der Linden et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][18][19][20] Only a few studies have been done in vivo. 21 In this study, we augmented cancellous screw fixation in vivo using rabbits older than 1 year, in which the growth plates had already closed.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Some authors showed that CPC was also useful for augmenting screw fixation. [18][19][20] CPC is an injectable, nonexothermic cement. CPC is slowly resorbed and replaced with living bone, 24 but the mechanical strength of CPC is inferior to that of PMMA.…”
Section: Discussionmentioning
confidence: 99%